ANALISIS KETERAMPILAN SHOOTING SEPAK BOLA: EFEK POWER DAN PERCAYA DIRI ATLET.: Indonesia - Rizky, Elfera (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2020)
The study purpose: Analysis path study aims to obtain information about the influence of leg explosive power, coordination and self confidence on shooting skill of football. Materials and methods: The sample taken by using total sampling technique as many 30 athlete. Based on the hyphotesist and This research uses a quantitative approach, survey methods with tests and measurements. Results. the researcher concluded that three is positive between leg explosive power and shooting skill by 0,437 (43,70%) There are positive influences between self confidence of shooting skill by 0,178 (17,80%) and the effect of the total effectiveness of the two variables is 0.615 or 61.50% so that the error variable is 38.50 influenced by external variables. Conclusions: This study concludes that it is true that there is positive effectiveness of leg muscle power variables, confidence in soccer shooting skills.